Anthropometry–Kansei for ergonomic assistive device design - Meri Andriani; Dewiyana Dewiyana; Taufan Arif Adlie; Nurmalawati Nurmalawati; Yusri Nadya; Leni Putma Sari; Bayu Revanza; Novianda Novianda; Yusnawati Yusnawati (Politeknik Negeri Lhokseumawe, 2026)
Manual work using non-ergonomic tools at the packaging station causes workers to bend over for long periods. This condition can increase the risk of Musculoskeletal Disorders (MSDs), thereby reducing worker productivity. The objectives of this study were to determine the greatest pain complaints from workers, design ergonomic aids to reduce MSDs complaints, and analyze worker responses to the ergonomic aids created. The methods used included worker anthropometric measurements, percentile determination, statistical tests to ensure data usability, and Kansei Engineering to identify worker interest in the tool. Results and discussion, popliteal length, popliteal height, and hip width are the dimensions used to design the tool. All dimensions were tested statistically. In the data sufficiency test, all data were declared valid, the data reliability test was declared reliable, and the data normality test stated that the data were normally distributed. The percentile used was the 50th percentile. Worker responses to the tool were evaluated using Kansei Engineering using nine Kansei words. All Kansei words were declared valid with values (0.407- 0.850) exceeding the r-table value, and the reliability test (0.707- 0.791) was declared greater than the Cronbach Alpha limit (5%), so all Kansei words were reliable. In conclusion, the ergonomic aids for packaging workers have a length of 43.65 cm, a height of 44.40 cm, and a width of 33.35 cm, while the evaluation of the aids produced seven descriptors with the highest scores, namely comfortable to use (0.940), safe to use (0.935), light (0.911), easy to use and move (0.913), simple design (0.920), flexible to use (0.951), and very functional when used in the workplace (0.938).